(untitled) (Washington, D.C., 2009)
Acknowledging the stupendous improvement in health care in China after the triumph of the Communist revolution in 1949, researchers from The World Bank explain that the country's needs have changed with the recent triumph of capitalism and here present the culmination of the Bank's analytic and advisory activities regarding China's rural health sector. They discuss China's health challenges now, the rural health reforms of the 2000s, the next decade, financing insurance coverage, improving service delivery as a question of incentives, enhancing accountability and incentives in public health, and the longer-term reform agenda.
Keywords: Rural health services,Health care reform,Insurance, health; China,China,China